Analysis of project management “supplier development project” in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2022)
The establishment of links between small and medium-sized enterprises (hereinafter referred to asSMEs) and foreign investors/multinational companies in Kazakhstan primarily depends on the favorableconditions imposed by the state for such investors.Business relationships with SMEs provide large firms with channels that reduce costs, increase productivity,enhance reputation, access local knowledge, and establish themselves in the local market. Activelyexpanding and strengthening business ties has been a major priority for the pilot of the KazakhstanSupplier Development Project (hereinafter referred to as SDP).Given the fact that large firms operating or planning to operate in Kazakhstan may find it difficult tofind SMEs offering relevant products and services, as well as to assess their qualifications and obtain theinformation needed to reduce risk when conducting transactions with them, SDP plays an important rolein providing information and matchmaking services.The main purpose of this article is to analyze the management of a pilot PSA project in Kazakhstan.The authors considered the main stages of the project implementation and their results, proposed appropriaterecommendations to prevent possible risks during the implementation of the second and subsequentcycles. A systematic approach and a method of data analysis were used in the study.Key words: competitiveness, public administration, supplier, project management, SMEs, industry,multinational companies.